2022
DOI: 10.1136/archdischild-2022-324442
|View full text |Cite
|
Sign up to set email alerts
|

Offshore detention: cross-sectional analysis of the health of children and young people seeking asylum in Australia

Abstract: ObjectiveTo describe the health and well-being of children and young people (CYP) seeking asylum subjected to Australia’s immigration policy of indefinite mandatory detention on Nauru.DesignCross-sectional analysis of a cohort of CYP seeking asylum.SettingAustralian paediatric clinicians from 10 health services completed detailed health assessments around the time of transfer from Nauru, mostly to Australia.ParticipantsSixty-two CYP who were ≤18 years on entry into offshore immigration detention on Nauru betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a study using data collected during the 2014 Australian Human Rights Commission Inquiry into Children in Immigration Detention, Mares (2016) found extremely high rates of mental disorder in both adults and children detained on Christmas Island, offering further evidence of the profound negative consequences of prolonged immigration detention for health. A recent cross-sectional analysis of a cohort of children and young people subjected to detention on Nauru ( n = 62) have also shown that the vast majority of the cohort had physical health (89%) and mental health (79%) concerns, including self-harm or suicidal ideation/attempt (45%); as per the study’s findings, mental health concerns were also more likely in children and young people who had been held in detention for a year or longer (Amarasena et al , 2023). Gleeson (2016) has also documented cases of self-harm and suicide attempts by offshore detainees, highlighting the psychological toll of prolonged detention and the harsh living conditions in RPCs on Manus and Nauru.…”
Section: Introductionmentioning
confidence: 65%
“…In a study using data collected during the 2014 Australian Human Rights Commission Inquiry into Children in Immigration Detention, Mares (2016) found extremely high rates of mental disorder in both adults and children detained on Christmas Island, offering further evidence of the profound negative consequences of prolonged immigration detention for health. A recent cross-sectional analysis of a cohort of children and young people subjected to detention on Nauru ( n = 62) have also shown that the vast majority of the cohort had physical health (89%) and mental health (79%) concerns, including self-harm or suicidal ideation/attempt (45%); as per the study’s findings, mental health concerns were also more likely in children and young people who had been held in detention for a year or longer (Amarasena et al , 2023). Gleeson (2016) has also documented cases of self-harm and suicide attempts by offshore detainees, highlighting the psychological toll of prolonged detention and the harsh living conditions in RPCs on Manus and Nauru.…”
Section: Introductionmentioning
confidence: 65%
“…Separate studies are being conducted regarding the health of asylum seeking CYP residing in Australia. 59 The extended 11 year time period allows for analysis of the trends over time. Nonetheless, this study is not longitudinal in design which limits predictive analysis.…”
Section: Discussionmentioning
confidence: 99%